Participatory Communication in Community-Based Tourism Development in Bireuen - Satria M, Deddy; ., Subhani; Ginting, Reza Pahlevi (Journal of Ecohumanism, 2024)
This study examines community participation in tourism development, especially in Community Based Tourism (CBT). By referring to the concept of tourism communication, this study aims to provide an overview of the role of individuals or community groups in encouraging the growth of tourist destinations. This study is expected to identify inhibiting and supporting factors in the implementation of participatory communication, as well as formulate recommendations to strengthen community participation in tourism development. Therefore, the selection of locations and informants, namely nature tourism business actors and the Regency Tourist Bireuen , is considered appropriate because it is in accordance with the characteristics of the research. The use of qualitative methods is expected to answer all questions that will be studied in this study.